Designing polymer crystallinity: An industrial perspective. Issue 2 (12th September 2018) - Mileva, Daniela; Tranchida, Davide; Gahleitner, Markus
Abstract: More than 50% of the thermoplastic polymers applied globally are semi‐crystalline, making crystallization part of the material and component design process for these materials. The mechanical and optical performance, but also the long‐term stability of the final articles and applications will depend upon three major groups of influence factors: Polymer structure and monomer composition, additive addition (especially nucleation) and blending with secondary components, and processing parameters. In the present review, we try to establish a connection between these three areas, the resulting combination of crystallinity and morphology, and the final application properties. Examples are drawn from the two major polyolefins, polyethylene and polypropylene, technical polymers like polyamide and polyester, but also polymers from renewable sources like poly(lactic acid). Abstract : To understand the overall performance of a part produced from a semi‐crystalline polymer for a specific application, one must consider all steps in its history, from the polymerization through additivation and compounding to processing and post‐processing operations. Using examples from polyolefins, technical polymers and even polymers from renewable sources, the present review shows how contributions from the three areas can be combined in designing polymer crystallinity.